2005
DOI: 10.1007/s00134-005-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral Care Reduces Incidence of Ventilator-Associated Pneumonia in ICU Populations

Abstract: Pulmonary nosocomial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
2
27

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(169 citation statements)
references
References 32 publications
5
134
2
27
Order By: Relevance
“…10 Oropharyngeal colonization with potentially pathogenic microorganisms is crucial in the pathogenesis of VAP. Oral care regimens that improve oral health status and modulate bacterial overgrowth could reduce the development of nosocomial VAP.…”
mentioning
confidence: 99%
“…10 Oropharyngeal colonization with potentially pathogenic microorganisms is crucial in the pathogenesis of VAP. Oral care regimens that improve oral health status and modulate bacterial overgrowth could reduce the development of nosocomial VAP.…”
mentioning
confidence: 99%
“…In a nonrandomized trial, 1248 patients in a medical-surgical ICU received oral care with a toothbrush and povidone-iodine swab. 21 Neuroscience patients accounted for 3% of the study population, but patients undergoing ICP monitoring were not identified. In the one study in which ICP was recorded during unspecified oral care (tooth brushing or swabs), ICP was stable in 879 recordings among patients with ICP values less than 20 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, oral care has been shown to be effective in the prevention of pulmonary infections, including aspiration pneumonia (Segers et al, 2008; Of these cases, because contamination of the oral cavity or pharynx in patients receiving artificial respiration can lead to Ventilator-Associated Pneumonia (VAP), a serious form of pneumonia, the importance of oral care during the acute phase has become widely known (Feider et al, 2010;Hutchins et al, 2009;Mori et al, 2006). Because perioperative artificial respiration is a commonly performed procedure, prevention of VAP is a major issue for the general care of patients.…”
Section: Introductionmentioning
confidence: 99%